Trajnostno hotelirstvo: Pristop ničelinih odpadkov v Ribno Alpine Resort - Crnogaj, Katja; Gajšt, Nataša (Študije primerov EPF: Razvoj, trajnost in inovacije v poslovni praksi 2024, 2024)
Ribno Alpine Resort is Slovenia's first certified zero-waste hotel, highlighting an innovative approach to sustainability in the hospitality industry. The hotel’s zero-waste policy focuses on minimizing waste production through composting, recycling, and reducing single-use materials. This case study examines the steps taken by Ribno Alpine Resort to achieve zero-waste certification and the impact of its sustainable practices on operational efficiency, guest satisfaction, and environmental preservation. Additionally, it explores the challenges faced by the resort, including sourcing sustainable materials and managing costs, and strategies to address these challenges. The case exemplifies the economic, environmental, and social benefits of the zero-waste approach and demonstrates its potential as a replicable model for other businesses in the hospitality industry. By exploring the journey of Ribno Alpine Resort, this case aims to provide valuable lessons for businesses committed to reducing their environmental impact while maintaining high standards of service.